Pengaruh Pengalaman Prakerin, Self Efficacy dan Internal Locus of Control Terhadap Kesiapan Kerja Siswa SMK di Bidang Akuntansi - Niki Ayu Puspitasari; Moh Danang Bahtiar (Program Studi Pendidikan Akuntansi Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2022)
Unemployment in Indonesia is dominated by SMK graduates. The low soft skills possessed by SMK students is one of the causes. The study was conducted to examine the effect of internship experience, self-efficacy and internal locus of control on job readiness in the accounting field. The study was conducted at SMK Wachid Hasyim Surabaya with the main focus of class XII AKL with a population of 71 students which was then used as a saturated sampling. Data were collected using documentation and questionnaire techniques. This research is included in quantitative research. Hypothesis testing is done by using multiple linear regression analysis technique. The results of the analysis show that partially there is a significant influence of internship experience, self-efficacy and internal locus of control on the work readiness of students in the accounting field. Simultaneously also showed a significant influence of internship experience, self-efficacy and internal locus of control on the job readiness of accounting students.